Pengaruh Inovasi Produk, Strategi Pemasaran, dan Label Halal Terhadap Keunggulan Bersaing Pada UMKM Desa Tangkit Baru Kecamatan Sungai Gelam - Iis Ariska; Titin Agustin Nengsih; Solichan Solichan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to identify and analyze the influence of independent variables on the dependent variable. The method used in this research is quantitative. The sample in this study consists of 80 SMEs in Tangkit Baru village, Sungai Gelam district. This study employs multiple linear regression analysis and conducts hypothesis testing using T-tests and F-tests, as well as analyzing the coefficient of determination. The results of this study indicate that Product Innovation (X1) has a significant effect on Competitive Advantage (Y) with a t-value of 2.792, which is greater than the t-table value of 1.665, and a significance value of 0.007, which is less than 0.05. This means that Ha is accepted and Ho is rejected. Marketing Strategy (X2) shows a significant effect on Competitive Advantage (Y) with a t-value of 4.972, which is greater than the t-table value of 1.665, and a significance value of 0.000, which is less than 0.05. Thus, Ha is accepted and Ho is rejected. The Halal Label (X3) shows a positive but not significant effect on Competitive Advantage (Y) with a t-value of 0.012, which is less than the t-table value of 1.665, and a significance value of 0.859, which is greater than 0.05. Therefore, Ha is rejected and Ho is accepted. Collectively, (X1), (X2), and (X3) simultaneously affect (Y) with a significance value of less than 0.05 and an f-value much greater than the f-table value.